2/3+1/6+11/12=
First you need to change these fractions to equivalent fractions with a common denominator.
If you post the equivalent fractions, we'll be glad to help you solve this problem.
Solve the problem and reduce to lowest terms? 2/3+1/6+11/12=
3 answers
(2/3)=(2*4)(3*4)=(8/12)
(1/6)=(2*1)/(2*6)=(2/12)
2/3+1/6+11/12=
=(8/12)+(2/12)+(11/12)
=(21/12)
=(12+9)/12
=(12/12)+(9/12)
=1+(3*3)/(3*4)
= 1 3/4
=(4/4)+(3/4)
=7/4
(1/6)=(2*1)/(2*6)=(2/12)
2/3+1/6+11/12=
=(8/12)+(2/12)+(11/12)
=(21/12)
=(12+9)/12
=(12/12)+(9/12)
=1+(3*3)/(3*4)
= 1 3/4
=(4/4)+(3/4)
=7/4
6 ⅚ – 17/18